Percepção entre dirigentes, atletas e técnicos sobre o Projeto Talento Olímpico Paranaense do período 2012 a 2016 na modalidade de atletismo - Bruno Marques Fidelis; Layla Mariana Maiante Pinto Antonechen; Carlos Antônio Izidoro Koch (Universidade Estadual do Oeste do Paraná, 2017)
The aim of this work was to analyze the perception of athletes, coaches and directors in relation to the Project TOP (Talento Olímpico Paranaense). The work was methodologically organized according to the Quali-Quanti type research, and was also descriptive. The instrument used for data collection was a semi-structured interview with a non-fixed route; a digital recorder and a notebook were used for taking notes. As sample, there were 16 individuals, being 4 of them coaches of athletics, that have athletes inside the project; 4 directors (2 from the Athletics Federation of Paraná and 2 from the Secretary of Sport and Tourism of Paraná) and 8 athletes from Athletics. The analysis of the results started through the readings of 16 interviews transcribed by the researcher, and throughout these readings a process of categorization of responses was carried out to subserve their analysis. From this, the data were presented in tables for a better understanding of the results. With the research, it was verified that the answers presented by the athletes are simpler, and try to express their side, pointing out only what matters at the moment, which is to guarantee the scholarship for the next stages of the project and receive the amount in money that the Project has undertaken to provide. It is concluded, therefore, that the perception of the athletes is different in relation to that of the directors and coaches, because they are in a different hierarchical position, playing different roles, however, the perception of the directors and coaches are similar, which came to similar responses regarding the TOP in the state.